2022
DOI: 10.1108/ijefm-04-2022-0036
|View full text |Cite
|
Sign up to set email alerts
|

Post-pandemic intention to participate in the tourism and hospitality (T&H) events: an integrated investigation through the lens of the theory of planned behavior and perception of Covid-19

Abstract: PurposeThis paper aims to predict the post-pandemic intention of Indian consumers to participate in tourism and hospitality T&H events by incorporating the perception of Covid-19 (PCOV) into the theory of planned behavior (TPB). It also examines the relationship among attitude, subjective norm, perceived behavioral control, behavioral intention and PCOV.Design/methodology/approachThis research employed a quantitative research technique, with data collected using an online questionnaire-based survey from Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Despite its simplicity, the Theory of Planned Behavior (TPB) has found extensive application in various contexts of innovation. These contexts include organic food purchase intentions (Teixeira et al, 2022), the adoption of e-library services (Rahmat et al, 2022), intentions to use promo codes (Hammouri et al, 2022), Green Hotel practices (Kim, 2023), the tourism industry (Özel & Çoban, 2022), hospitality (Al Rousan et al, 2022), health-related matters (Shanka & Gebremariam Kotecho, 2023), energy-related decisions (Tan et al, 2023), financial considerations (Sobaih & Elshaer, 2023), mobile payments (Belanche et al, 2022;Sun et al, 2020Sun et al, , 2022, and various other domains.…”
Section: The Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Despite its simplicity, the Theory of Planned Behavior (TPB) has found extensive application in various contexts of innovation. These contexts include organic food purchase intentions (Teixeira et al, 2022), the adoption of e-library services (Rahmat et al, 2022), intentions to use promo codes (Hammouri et al, 2022), Green Hotel practices (Kim, 2023), the tourism industry (Özel & Çoban, 2022), hospitality (Al Rousan et al, 2022), health-related matters (Shanka & Gebremariam Kotecho, 2023), energy-related decisions (Tan et al, 2023), financial considerations (Sobaih & Elshaer, 2023), mobile payments (Belanche et al, 2022;Sun et al, 2020Sun et al, , 2022, and various other domains.…”
Section: The Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…How closely someone identifies with nature is strongly allied to the attitudes that he or she acquires (Schultz et al, 2004). Several studies have found that AT had the most significant affiliation (Al Rousan et al, 2022;Dybsand and Stensland, 2022;Fenitra et al, 2021;Huang et al, 2014;Lin and Huang, 2021;Miller, 2019;Sujood et al, 2021a;Xu et al, 2021;Zhang et al, 2022) or simply no affiliation (Esfandiar et al, 2020) to the intention concerning national Urban tourists' intention towards national parks parks. Based on the foregoing empirical and conceptual grounds, the hypothesis is proposed as follows:…”
Section: Attitude (At)mentioning
confidence: 99%